Ecological Study of Epipelic Algae in AL- Diwaniyah* River/Iraq - M.Alkam, Foad; H.Yassir, Sanaa (Al-Qadisiyah Journal of Pure Science, 2017)
The present study is deal with the relationship between some physical –chemical characteristic and epipelic algae in Al-Diwaniyah River ,also called ( Shatt Al-Diwaniyah) for six months started from November 2012 to April 2013.Three sites were chosen on the river, the first in the north of Al-Diwaniya city while the second is after the first about ten kilometers and the third site is after the second about thirteen kilometers.The results of the study cleared the water of the river was good oxygenated ,very hardness and tend to be alkalinity as the other water in Iraqi rivers .This study identified (234)species belong to four classes which started of Bacillariophyceae,Cyanophyceae,Chlorophyceae and Euglenophyceae in respectively.Som genera consisting of larg number ofspeciesas(Nitzschia, Navicula,Cymbella,Amphora,Achnanthus,Gomphonema and Oscillatoria).Species were appeared in the period of study were consisting of(Nitzschia palea, Navicula cincta ,Synedra ulna,Surirella ovate,Spirulina gignata and Oscillatoria Formosa).There was one peak in months of spring specially in (March and April).